Effect of Choline Chloride Supplementation on Broiler Chicks Fed Leucaena leucocephala Seeds - Ahmed, Mohamed Elamin; Abdelati, Khadiga Abbas (International Journal of Poultry Science, 2011)
This experiment was carried out to assess the effect of feeding leucaena seeds supplemented with choline on broiler chicks’ performance. Two levels of choline chloride (0, 0.1%) were added to three levels of leucaena seeds (0, 6 and 12%) and incorporated in broiler starter and finisher diets. All performance parameters were depressed with the inclusion of leucaena seed diets. PCV% of birds fed any level of leucaena seed diets was not significantly different compared to control. Plasma GOT, ALP, Na, Pi, K and globulin were not affected by the dietary treatments. Plasma cholesterol of birds fed leucaena seed diets was significantly lower than that of control. Leg score of birds fed leucaena seed diets was significantly (p<0.05) poorer compared to the control except for birds fed 6% choline supplemented leucaena seeds.